“Unpacking” cultural differences in social anxiety between Japanese and European Americans: the roles of threat appraisal and attentional bias - Krieg, Alexander; Xu, Yiyuan (Frontiers in Psychology, 2023)
Introduction Cultural differences in self-reported social anxiety between people of East Asian heritage and European heritage may be related to differences in independent and interdependent self-construals, which potentially influence the processing of social threat. Methods We examined the roles of two different aspects of threat bias: threat appraisal (Study 1) and attentional bias (Study 2) to explain cultural group differences in social anxiety between Japanese and European American college students. Results Study 1 demonstrated that sequential mediations of lower independent self-construal and higher appraisal of threat among Japanese could explain their higher social anxiety compared to European Americans. However, Study 2 failed to find the relation between cultural group differences in self-construals and attentional bias. In addition, the cultural group differences in attentional bias were unexpectedly due to stronger selective attention toward neutral stimuli among European Americans, rather than bias toward social threat among Japanese. After selective attention was experimentally manipulated, there were significant cultural group differences in self-reported social anxiety and anxious behavior in a speech task. Discussion These conflicting findings suggested that an alternative theoretical framework other than the self-construal theory might be needed to fully account for cultural differences in attentional bias in explaining cultural group differences in social anxiety.